2013
DOI: 10.2112/si_69_9
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Factors Related to the Persistence of Subsurface Oil from the Exxon Valdez Oil Spill

Abstract: I www.JCRonline.org Nixon, Z.; Michel, J.; Hayes, M.O.; Irvine, G.V., and Short, J., 2013. Geomorphic factors related to the persistence of subsurface oil from the Exxon Valdez oil spill.Oil from the 1989 Exxon Valdez oil spill has persisted along shorelines of Prince William Sound, Alaska, for more than two decades as hoth surface and suhsurface oil residues. To hetter understand the distribution of persistent subsurface oil and assess the potential need for further restoration, a thorough and quantitative un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…39 Upon landfall, oil percolated through the highly permeable boulder armoring and became entrained in fine grained sediments located below. Natural breakwaters and headlands protect these beaches from wave exposure, 41 and limited hypoxic groundwater flow through the relatively impermeable fine sediments minimizes the potential for microbial degradation of the oil. 42 Most of the subsurface oil is currently found in Prince William Sound below 10−20 cm of clean sediments.…”
Section: Introductionmentioning
confidence: 99%
“…39 Upon landfall, oil percolated through the highly permeable boulder armoring and became entrained in fine grained sediments located below. Natural breakwaters and headlands protect these beaches from wave exposure, 41 and limited hypoxic groundwater flow through the relatively impermeable fine sediments minimizes the potential for microbial degradation of the oil. 42 Most of the subsurface oil is currently found in Prince William Sound below 10−20 cm of clean sediments.…”
Section: Introductionmentioning
confidence: 99%
“…According to Nixon and Michel (2018), these oil residues are typically located in finer-grained sand and gravel sediments, often under an armor of cobble-or boulder-sized clasts, in areas with limited groundwater flow and porosity. According to Nixon et al (2013) the oil persistence, nearly 20 years after the Exxon Valdez oil spill on the intermittently exposed gravel beaches, is due to a complex interaction between small-scale geomorphic features (e.g., armoring) that proved shelter from the local incident wave energy. They documented subsurface oiled layers down to an average burial depth between 13.6 and 18.6 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified factors that affect the behavior and persistence of oil on the shorelines of PWS and the Gulf of Alaska in the more than 20 years since the spill. As part of these studies, the presence of both surface and subsurface oiling and the presence of geomorphic factors that led to oil persistence have been documented at discrete locations; however, these studies are largely descriptive, and limited quantitative extrapolation was possible. We used survey data describing the presence of subsurface oil in excavated pits together with synoptic predictor variables to derive a series of models for use in generating calibrated probabilities of encountering subsurface oil of various types at all locations.…”
Section: Methodsmentioning
confidence: 99%
“…Review of previous investigations indicated that the primary drivers of control of long-term oil persistence after oil has been stranded are initial oil loading, shoreline geometry and geomorphology, and wind wave exposure. Based on this review, we derived a series of raster layers describing oiling and physical variables thought to influence and control the presence and persistence of subsurface oil in PWS.…”
Section: Methodsmentioning
confidence: 99%